The role of due diligence in cross-border acquisitions - Kaariste, Marjut (My University, 2013)
Mergers and acquisitions (M&A) have become an important strategy for international expansion, even though numerous acquisitions fail to achieve their financial and strategic objectives. The risk associated with transactions partly depends on the extent to which the insight into the target company actually holds true. Due diligence is performed to eliminate this information asymmetry. Due diligence is an audit conducted prior to the planned transaction. It can be described as a purposeful and systematic investigation of business opportunity and risk during on-going sale negotiations. The importance of due diligence is emphasized widely in the academic literature as well as among M&A practitioners. On the other hand, researches and practitioners have differing views on what and how much is enough for a due diligence audit. Therefore, this study examines the role of due diligence in a cross-border acquisition process. The main objective of the research is fulfilled by examining the reasons for conducting due diligence, recognizing the elements affecting effective due diligence and analyzing the need and opportunities for enhancing the utilization of due diligence. For the empirical part of this qualitative study five expert interviews were conducted among experienced Finnish acquirers and advisors. In addition, five expert interviews conducted for a distinct study were utilized as a secondary source of data. The results of this study present fundamental reasons for conducting due diligence. However, conducting due diligence is not always self-evident. Doubtful attitude towards due diligence exists, though it is exceptional. Carefully planning the focus of due diligence and compiling and managing the team conducting due diligence are identified as the main elements affecting effective due diligence. Altogether, due diligence can have plural roles which in this study are categorized as the confirmatory, preparative, and cross-functional roles of due diligence. The older academic literature tends to emphasize the confirmatory role whereas the current academic discussion also supports the preparative role of due diligence. It can be argued that the roles of due diligence differ among experienced due diligence practitioners based on several factors. In attempt to increase the value of due diligence for acquirers, more than one role of due diligence is likely to exist. As a result of the different approaches and the controversy regarding the concept of due diligence, the demand for a new, wider definition of due diligence can be claimed to exist.